Phylogenomic synteny reveals paleohexaploid-derived genomic blocks across Asteraceae - Tao Feng; Michael McKibben; John Lovell; Richard Michelmore; Loren H. Rieseberg; Michael S. Barker; M. Eric Schranz (Proceedings of the National Academy of Sciences, 2026)
The Asteraceae (Compositae) is the largest flowering plant family, ubiquitous in most terrestrial communities, and morphologically diverse. A two-step, ancient whole genome triplication (paleohexaploidization) occurred at approximately the same time as the evolutionary innovation and adaptive radiation of the family during the middle Eocene. Despite its importance, the consequences of this triplication have yet to be tracked in context of the Asteraceae genome evolution. To do so, we applied a synteny oriented phylogenomic analysis of 23 Asterales genomes. We identified 16 genomic groups that date back to the common diploid ancestor of all Asteraceae. Each group underwent triplication, resulting in 48 genomic blocks (16 × 3) that collectively represent the ancestral Asteraceae genome, excluding the early-diverging lineages which do not share the second step. We then analyzed the evolutionary dynamics of the 48 genomic blocks across the Asteraceae phylogeny. We found that modern Asteraceae genomes are genetic mosaics of three progenitor genomes, shaped by genomic exchanges, chromosomal rearrangements, and gene fractionation. One hundred fifty-seven genes retained three paleohexaploid-derived syntenic paralogs across most Asteraceae species. Transcription factors and auxin-related genes are significantly overrepresented in these triplets, and expression of the paleohexaploidy paralogs is spatiotemporally differentiated. These genes are involved in the development of floral capitula, a remarkable morphological innovation of the family. The discovery of the 157 triplicated genes can direct further study to understand the evolutionary innovation, and the synteny-phylogenomic framework provides a comparative framework to characterize newly sequenced Asteraceae genomes.